Anticancer and Antiviral Diketopiperazine Produced by the Red Sea Endophytic Fungus Penicillium chrysogenum - Hawas, Usama W.; Abou El-Kassem, Lamia T. (Letters in Organic Chemistry, 2019)
Scale-up fermentation of the endophytic fungus Penicillium chrysogenum in biomaltpeptone media followed by cytotoxicity-guided fractionation led to the isolation of haenamindole, an unusual diketopiperazine (DKP) alkaloid, along with other five known DKPs. Haenamindole was elucidated on the basis of comprehensive 1D and 2D NMR spectroscopic including 15N-HSQC and 15NHMBC and mass spectrometric analyses. The compound possesses the secondary hydroxamic acid functionality of N-piperazindione ring system confirmed by methylation in sodium dimethyl sulfate and dry dimethylformamide to yield haenamindole-22-N-methyl ether. However, haenamindole demonstrated weak HCV protease activity with an IC50 value of 76.3μM, its cytotoxicity profiling in a panel of up to 12 cell lines indicated significant cytotoxicity of the compound with pronounced selectivity for colon-38 cancer cells compared to the human normal cells.
Keywords: endophytic fungus